Education: The Use of Vitamins and Drugs for Covid 19 During the Pandemic in Mangkurakyat Village, Cilawu Garut District - Retty Handayani; Anggi Riswan Safarinoer; Muhamad Abdilah; Neng Elsa; Nida Amalia; Nurfajriyanti Nurfajriyanti; Raja Andri Hidayat (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The increasing number of positive cases of covid 19 in various regions and the high death rate have led to a lot of recommendations to increase endurance in various media, this has led to